Influence of a courtyard with a glazed roof on the thermal comfort of a house in the city of Huaraz - Corrales Picardo, Miguel Ronald (2022)
The work determined the influence of a glazed roofed courtyard to improve the thermal comfort of a minimum control house located in the city of Huaraz - Peru; for which, the same dwelling was compared before covering the courtyard and after the intervention. The thermal calculation was carried out through the analysis of heat gains and losses. In conclusion, the courtyard with a glazed roof increased the temperature by around 1.97°C, improving the thermal comfort of the dwelling, going from an internal average temperature of 17.17° to 19.4°C.